Influence of Water Stress and Spraying With Eucalyptus Leaves Extract on Growth and Yield of Eggplant Solanum melongena L. - Albajary , Ahmed Ibrahim Kalaf; Sheikh, Qotaiba Saleh; Mohammed, Dalal Fattah; Abdalla, Hero Farman; Karim, Aisha Mohammed Abdul; Gadallah, Riyadh Ahmed; Hadres, Ibrahim Ahmed; Abood Fares, Mohammed Ali (American Journal of Biodiversity, 2026)
A field experiment was conducted at the Research Station of the Northern Technical University / Polytechnic college - Hawija during the spring season of 2024. The experiment was designed according to the randomized complete block design (RCBD). This study included two factors : the first factor was water stress at two levels (irrigation for 30 minutes W1, irrigation for 15 minutes W2) and the second factor was spraying with eucalyptus leaves extract at three levels (without spraying, spraying at a concentration of 1 ml L-1, spraying at a concentration of 2 ml L-1). planted the seeds of the eggplant variety Thuraya, in cork plates (209) a plate was designated and using a growing medium for seedlings from the Dabana Agricultural Company. It is considered which is a prolific variety and is used in open cultivation. Plant seeds were planted on the date 15 / 7 /2024 when it reached the appropriate stage for planting in greenhouses and then was transferred to the field on the date 8 /10 / 2024 . the show results that first level of irrigation (W1) It achieved significant differences in most of the studied parameters (Plant height , chlorophyll content and Total yield) and its rate were (67.08 cm , 63.76 and 7.51 ton ha-1) respectively , While the level of eucalyptus leaves extract (1 ml L-1) gave the highest rates for the above parameters compared the others levels and reached (67.00 cm , 69.52 and 8.65 ton ha-1) respectively.